Between Intent and Illness: A Look at Malingering vs. Factitious Behaviours - Amy Anyi (BJPsych Open)
Aims: Presented is a 33-year-old gentleman with a diagnosis of emotionally unstable personality disorder (EUPD) well-known to mental health services, including inpatient, community, liaison, and psychological care teams, with a long-standing history of self-harm and suicide attempts, which included deliberately placing himself in high-risk public areas which have at times resulted in detention under mental health legislation.